The Proportion of Problem Solving and Scientific Reasoning Skills in Biology References - Dhora Vasminingtya Reginaning Charysma; Sri Widoretno; Sri Dwiastuti (Intelektual Pustaka Media Utama, 2018)
Problem-solving is a vital component under the cognitive standard of the 21st century skills for preparing students to face global competition. Problem-solving supported by another skill, one of which is scientific reasoning. Research objective is to analysis profile content and context of Biology references by interaction of problem-solving and scientific reasoning aspects. Research procedure applied Toulmin Argument Pattern (TAP) as a basic framework to identify the scientific reasoning aspects. Data obtained from the questionnaire, survey, and analyzed descriptively. Result indicates that the majority of Biology references does not required of balance proportion between problem-solving and scientific reasoning aspects. The lower aspect both of content and context was located in explore and Look back for Ground and Rebuttal aspects. In addition, this result can be used to inform future development of instruction and assessment problem solving and scientific reasoning skills.